The glucose uptake velocity and ability of target tissue cells in the elderly men (in vivo) - Wasilah Rochmah Wasilah Rochmah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Age is one of the impaired glucose tolerance risks. Impaired glucose tolerance may be caused by the decrease of pancreatic B cells insulin secretion, or by the decrease of target tissue cell glucose uptake. Glucose tolerance tests which were conducted in the elderly, showed that plasma insulin concentrations at 120th minute were still higher than at minute-0 (at fasting time), while blood glucose levels were still high. It generated an impression that insulin inefficiency exist in the elderly.Objective: To reveal that the cause of insulin inefficiency in the elderly is due to the decrease of target tissue cell glucose uptake velocity and/or in decrease uptake ability.Methods: Elderly men subjects and young men comparable controls were given 130mU/kg L8M/hour insulin and 20g% dextrose infusion, while blood glucose level have to be maintained in euglycemic situations (euglycemic clamp test). In 30 minutes with stable blood glucose level, the amount of 20% dextrose infusion were calculated as glucose uptake in 30 minute (euglycemic clamp time). From this results the glucose uptake velocity and ability (glucose uptake ability = ratio between glucose uptake velocity and plasma insulin concentration = insulin sensitivity index) between the elderly and the young men were compaired by t-test.Results: Euglycemic clamp tests were conducted to 4 elderly men of 65-74 years old, and 4 young men of 21-30 years old as controls. The results showed that the velocity of glucose uptake by the target tissue cells in those elderly men were significantly (p<0.05) lower (10.08 f 2.34 mg/kg LBM/min.) than young men group (17.78 ± 5.49 mg/kg LBMlmin.). One elderly men showed the lowest difference (0) of insulin sensitivity index compared to one control subject. In the remaining three (75%) subjects the average of insulin sensitivity index (0.11 f 0.03) showed a significant difference (p<0.05) compared to young men group 10.19 f 0.04).Conclusions: The result of this study indicated that the cause of insulin inefficiency in the elderly men was due to the decrease of glucose uptake velocity and ability.Key words: impaired glucose tolerance - pancreas B cells insulin secretion - velocity of glucose uptake ability of glucose uptake - euglycemic clamp technique.